Answer:
the proof is below
Explanation:
You want a proof by induction of the formula for the sum of consecutive even numbers.
Step 1: base case
The given formula is ...
Sn = n(n+1)
For n=1, the one-term sequence is the first term: 2. Its sum is 2.
2 = (n)(n+1) = (1)(1+1) = 2 . . . . . true
Step 2: n = k
For this step, we assume the formula is correct. Then ...
Sk = k(k+1)
Step 3: n = k+1
The sequence sum for k+1 terms is ...
2 + 4 + 6 + ... + 2k = k(k+1) . . . . . assumption from step 2
(2 + 4 + 6 + ... + 2k) +2(k+1) . . . . . one more term added; sum of k+1 terms
k(k+1) +2(k+1) . . . . . . . . substitute assumed value for (2 + 4 + ...)
(k +2)(k +1) . . . . . . . . . . factor out k+1
And the formula for k+1 terms is ...
= (k+1)((k+1) +1) . . . . . substitute (k+1) for n
= (k+1)(k+2) . . . . . . . perform the addition
Note that the sum of terms is (k+2)(k+1), and is identical to the formula for the same sum: (k+1)(k+2). (Remember, multiplication is commutative.)
(k+2)(k+1) = (k+1)(k+2) . . . . . QED